Regulation of reactive oxygen and nitrogen species by salicylic acid in rice plants under salinity stress conditions - Kim, Yoonha (PLoS One, 2018)
This study investigated the regulatory role of exogenous salicylic acid (SA) in rice and its effects on toxic reactive oxygen and nitrogen species during short-term salinity stress. SA application (0.5 and 1.0 mM) during salinity-induced stress (100 mM NaCl) resulted in significantly longer shoot length and higher chlorophyll and biomass accumulation than with salinity stress alone. NaCl-induced reactive oxygen species production led to increased levels of lipid peroxidation in rice plants, which were significantly reduced following SA application. A similar finding was observed for superoxide dismutase; however, catalase (CAT) and ascorbate peroxidase (APX) were significantly reduced in rice plants treated with SA and NaCl alone and in combination. The relative mRNA expression of OsCATA and OsAPX1 was lower in rice plants during SA stress. Regarding nitrogenous species, S-nitrosothiol (SNO) was significantly reduced initially (one day after treatment [DAT]) but then increased in plants subjected to single or combined stress conditions. Genes related to SNO biosynthesis, S-nitrosoglutathione reductase (GSNOR1), NO synthase-like activity (NOA), and nitrite reductase (NIR) were also assessed. The mRNA expression of GSNOR1 was increased relative to that of the control, whereas OsNOA was expressed at higher levels in plants treated with SA and NaCl alone relative to the control. The mRNA expression of OsNR was decreased in plants subjected to single or combination treatment, except at 2 DAT, compared to the control. In conclusion, the current findings suggest that SA can regulate the generation of NaCl-induced oxygen and nitrogen reactive species in rice plants.